2010
DOI: 10.4049/jimmunol.0904209
|View full text |Cite
|
Sign up to set email alerts
|

Direct CD4 Help Provision following Interaction of Memory CD4 and CD8 T Cells with Distinct Antigen-Presenting Dendritic Cells

Abstract: Accumulating evidence suggests that CD4 help is needed at the memory stage to mount effective secondary CD8 T cell responses. In this paper, we report that memory CD4 T cells can provide efficient help to memory CD8 T cells after interaction of the two lymphocytes with distinct dendritic cells. Provision of help to CD8 T cells required direct cell–cell contact and involved both IL-2 and CD40 ligation, within a CD4–CD8 T cell synapse. Thus, following antigenic interaction with APCs, activated memory CD4 and CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…3a). This period of activation with DCs in the presence of CD4 T cells was necessary for secondary expansion of resting memory CD8 T cells and for their differentiation into cytotoxic secondary effectors821. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…3a). This period of activation with DCs in the presence of CD4 T cells was necessary for secondary expansion of resting memory CD8 T cells and for their differentiation into cytotoxic secondary effectors821. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…If communication between CD4 T cells and other cells, including DC, B cells, CD8 T cells and macrophages, operates preferentially at relatively short range [54][59] then variable expression of cytokines by individual T cells may also increase the variability of the phenotypes of these other effector cells. For example, IL-2 drives CD8 cells toward a memory cell phenotype, whereas IFNγ induces the CD8 cells to become effector cells [60].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, agonistic anti-CD40 and anti-4-1BBL mAbs and peptide-pulsed DCs could not overcome the diabetes resistance of 17 T cell memory against viral (7,8,10), bacterial (9), and self-Ags (11) in the absence of CD4 + cells is defective, resulting in reduced survival of memory CD8 + cells and impaired responsiveness to secondary antigenic challenge. The CD4 + Th cell signals responsible for promoting autoregulatory CD8 + T cell memory formation remain unclear, but might be similar to those involved in effector T cell memory formation (24)(25)(26)(27). It has also been suggested that unhelped memory CD8 + T cells tend to commit suicide by secreting TRAIL in response to a secondary antigenic challenge (28).…”
Section: Discussionmentioning
confidence: 99%